O papel da espiritualidade no modelo dos 12 Passos dos Alcoólicos Anônimos, segundo profissionais da Psicologia - Benzecry, Denis Fred (2023)
This study proposed an investigation by addressing aspects involved in the recovery process for alcoholics. The objective was to explore as a clinical psychologist comprise possible relationships between spirituality and interventions, as well as discuss the moderating role of spirituality, as practiced in A. A. (Alcoholics (Anonymous). To this purpose, spirituality was prioritized, with emphasis on the 12 steps. Psychology authors who research articulations between clinical practices and spirituality in health and illness processes, point out that the recovery of alcoholics is a multidimensional and multidisciplinary process, whose goal is: to give conditions for the alcoholic to elaborate and implement a project of Life, with self-control and promotion of new social relations and that support it alternatively to alcoholism. The A.A.`s 12 step model is based on its own approach, that rests on spirituality as one of the main tools for treating alcoholism and preventing relapses by adopting a plural vision that facilitates the individual a reformulation in the way of living with quality. There was bibliographic research on alcoholism, about A.A., from its own literature, and about R/E (religion/spirituality), articulating such subjects. The next phase was field research through the online application of a quanti-qualitative survey, whose sample was made up of clinical psychologists who had primarily alcoholics as their patients. Spirituality has been considered, from the early days of A.A. to the present day, the foundation in its programming. This thesis suggests the compatibility of A.A.'s programming, the 12 steps, with other treatment strategies, not only in the theoretical framework, but in the analysis of field research. Regarding research on A.A., 34 articles selected from theoretical and empirical contents were clear in pointing out improvements, considering the criterion of increased abstinence days, reduced clinical interventions and treatment costs. Regarding spirituality, this study selected and analyzed 27 papers that have in common, both theoretical and empirically, the presence of positive influence of the practice of R/E in the establishment of health, especially the alcoholics. 91 Psychologists answered quantitatively about the contribution obtained by the practice of 12 steps in recovery and the result was 83% of relevance. As for the practice of spirituality, relevance reached 90%. Qualitative analysis suggests coherence with the previous survey. 78 Valid answers underwent textual data processing by IRAMUTEQ software. Words and expressions were divided into 5 classes: professionalism, recovery, motivation, transcendence and resilience. The incidence of the words: spirituality, God and faith stands out